READING NGUGI’S WEEP NOT, CHILD ALONG WITH ALICE WALKER’S WOMANISM - Adel El-Sayed Hassan (European Scientific Journal, ESJ, 2014)
Ngugi wa Thiong’o’s Weep Not, Child may be read as a novel about the anti-colonial strife of the Mau-Mau guerrillas against the English colonialists. It may also be read as a novel featuring the estrangement of the African people from their ancestral land. Further, it may be read as a novel about the experience of the African women in general. Still, Weep Not, Child can be read as a womanist novel concerned with the experiences of women of color. Drawing upon Alice Walker’s womanism and her theoretical writings about the gender issue and motherhood, this paper examines Weep Not, Child to demonstrate how womanist it is. The paper reveals that the female characters in the novel epitomize most, if not all, the characteristics of women underlying Walker’s definition of womanism. In addition, it indicates that the black women’s struggle against patriarchal oppression and their perseverance to educate their children materialize Walker’s theoretical views about gender and motherhood. The novel does not solely concentrate on the black experience, but it also takes the white position into consideration. The paper concludes that the novel incarnates the universalist attitude central to Walker’s womanism by pleading for connectivity, understanding and compatibility among races and genders.